Peningkatan Penjualan Melalui Pengemasan, Labelling dan Branding Produk di Desa Sukaratu Kecamatan Cikeusal Kabupaten Serang - Dien Sefty Framita; Dian Maulita (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2020)
Packaging, labels, and brands are one of the main attractions for products to increase sales. Community Service Activities are carried out in Cikeusal Subdistrict, Serang Regency, with the target of being business actors producing chips in Sukaratu Village, Cikesal District, Serang Regency. Community Service Activities are carried out with the aim of providing an understanding of the emping-producing citizens regarding the importance of packaging, labeling and branding on a product that can increase sales levels and will automatically increase their economic income. The socialization was adjusted to the problems and needs faced by emping entrepreneurs in Cikeusal District. The method of implementing the activity consists of three stages. The first stage of preparation includes pre-survey, team formation and coordination of teams and participants as well as preparation of training tools and materials. The second stage is the program implementation stage in the form of socialization. Socialization is carried out through outreach (presentation of material) and discussion. The third stage is the evaluation and reporting stage. Evaluation is carried out by comparing the conditions of the participants before and after the program implementation with the interview and observation methods. After that, a report was prepared. The material presented in the socialization was regarding the form of a legal entity and its important function of having a business license and business licensing mechanism. All stages of this activity have reached 100% implementation and have resulted in outcomes including understanding of community service participants about the importance of packaging, labeling and branding on a product.